2018
DOI: 10.18203/2394-6040.ijcmph20181205
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of elementary students about reproductive health (preliminary study on elementary school in Brebes district, Central Java, Indonesia)

Abstract: Background: Knowledge of elementary students about reproductive health in Indonesia still lack. There are so many students who did not know how to maintain good reproductive health. Efforts to give lessons reproductive health or sex education to elementary school age children today is still considering taboo, but this problem should be anticipated as soon as possible. To decrease maternal mortality rate and unmet-need needs innovation to educate students. Education about reproductive health is one of strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…The level of knowledge of respondents on reproductive health variables increased from 53.90% to 58.96%. This is similar to research by Nugraheni et al (2018), who found changes in the level of knowledge in 70 elementary school students regarding reproductive health. Before being given reproductive health education as many as 10 respondents (14.3%) were able to answer correctly.…”
Section: Discussionsupporting
confidence: 90%
“…The level of knowledge of respondents on reproductive health variables increased from 53.90% to 58.96%. This is similar to research by Nugraheni et al (2018), who found changes in the level of knowledge in 70 elementary school students regarding reproductive health. Before being given reproductive health education as many as 10 respondents (14.3%) were able to answer correctly.…”
Section: Discussionsupporting
confidence: 90%